A Systematic Review Of “Modern Matriarchy” Featuring The Khasi, The Mosuo, The Bribri, The Minangkabau, The Akana, The Umoja - Dyah Sulistyaningrum; Siti Drivoka Sulistyaningrum; Sri Sumarni (Universitas Muhammadiyah Semarang, 2023)
The term “matriarchy” should be retained, and a new structural description should be used to describe their fundamental structure, according to this study where the hypothesis depends on diverse concentrate on surviving native human advancements' financial, social, political, and social angles (Goettner, 2018). It will be demonstrated that matriarchy is consensus-based, gender-equal communities that foster peace and sustainability. Six examples include the Mosuo of Southwest China, the BriBri of Costa Rica, the Umoja of Kenya, the Minangkabau of Indonesia, the Akana of Ghana, and the Khasi of Northeastern India. The focus of this study is not on ethnographic parallels and contrasts, but on what constitutes them “matriarchies” and how the concept can accommodate variability, expanding our understanding of these civilizations. Conclusions summarize the conversation, emphasize the topics of politic and discuss the existences of modern matriarchy in the future.